N. F. S. Grundtvigs “Studier til en bibelsk Rimkrønike” (1828) set i lyset af hans samtidige kristeligt pædagogiske tanker - Riisager, Else (Grundtvig-Studier, 2010)
N. F. S. Grundtvigs “Studier til en bibelsk Rimkrønike” (1828) set i lyset af hans samtidige kristeligt pædagogiske tanker [N. F. S. Grundtvig’s “Studies for a Biblical Rhymed Chronicle” (1828) viewed in the light of his contemporaneous Christian-pedagogical thinking] By Else Riisager Grundtvig was engaged in communicating biblical and ecclesiasticalhistorical material in the form of hymns and songs which primarily appealed to children, young people and layfolk for practically the whole of his productive life. “Studies for a Biblical Rhymed Chronicle” from 1828 (Theologisk Maanedsskrift XIII, 145-181), which contains material from protohistory, is Grundtvig’s first attempt at a systematic publication of biblical-historical poetry. In the preface he expresses his aspiration to write biblical rhymed chronicles for children for use in schools. In his collected edition of the genre, Sang-Værk til Den Danske Kirke-Skole (1870; GSV II), the poetry from “Studies” is included as numbers 1, 2, 6, 7 and 8. The present article examines Grundtvig’s Christian-pedagogical thinking as regards the target audience at the time of publication and compares this thinking with his practice in “Studies” through a detailed analysis of Kain pløied rask i Vaar (GSV II, 6) and a more thematic presentation of the other poems. Examination of the prefaces of Grundtvig’s contemporary pedagogical publications reveals that the main purpose of the poems is Christological preaching based on the Apostles’ Creed. In practice the poems in “Studies” are Christian preaching, but not specifically Christological preaching. There is, however, nothing in the poems that speaks against a Christological context and there are numerous traits that address a Lutheran universe. Where the Christological preaching relating to the rendering of the Old Testament material is only implied, this is out of respect for the informative purpose. With regard to the genre of the poems, around 1828 Grundtvig’s preferred idea was to create biblical history in verse within the Christian pedagogical area, with genre-related traits from the medieval text, Den danske Rimkrønike. Verse is easier to read, learn and remember than prose; and by writing narratives about persons and events in verse, Grundtvig aspires to communicate the biblical material easily, vividly and animatedly. The intention of the poems is that they should be used as material for Christian teaching of Christian children at home and in connection with confirmation training. In practice, GSV II 6 and 7 are addressed to children and their parents and teachers, while GSV II 1, 2 and 8 have young persons as their primary intended recipients. Grundtvig was dissatisfied with the poems in “Studies” - not because of any deviation from his original intentions but rather because, in the event, the pedagogical intentions are not achieved. GSV II 1,2, and 8 are long and difficult to understand for the target audience. The poems are in all probability not lively enough to persuade children to listen to them, or – as Grundtvig himself phrases it - to persuade even himself that they are worth memorising. At this stage the genre of the individual items is neither hymn nor song, but rhymed biblical chronicle. “Studies for a Biblical Rhymed Chronicle” is a first attempt to start compiling a textbook in versified biblical history for Christian children, young persons and parents